High throughput single-cell genome sequencing gives insights into the generation and evolution of mosaic aneuploidy in Leishmania donovani. Issue 1 (10th December 2021) - Negreira, Gabriel H; Monsieurs, Pieter; Imamura, Hideo; Maes, Ilse; Kuk, Nada; Yagoubat, Akila; Van den Broeck, Frederik; Sterkers, Yvon; Dujardin, Jean-Claude; Domagalska, Malgorzata A
Abstract: Leishmania, a unicellular eukaryotic parasite, is a unique model for aneuploidy and cellular heterogeneity, along with their potential role in adaptation to environmental stresses. Somy variation within clonal populations was previously explored in a small subset of chromosomes using fluorescence hybridization methods. This phenomenon, termed mosaic aneuploidy (MA), might have important evolutionary and functional implications but remains under-explored due to technological limitations. Here, we applied and validated a high throughput single-cell genome sequencing method to study for the first time the extent and dynamics of whole karyotype heterogeneity in two clonal populations of Leishmania promastigotes representing different stages of MA evolution in vitro . We found that drastic changes in karyotypes quickly emerge in a population stemming from an almost euploid founder cell. This possibly involves polyploidization/hybridization at an early stage of population expansion, followed by assorted ploidy reduction. During further stages of expansion, MA increases by moderate and gradual karyotypic alterations, affecting a defined subset of chromosomes. Our data provide the first complete characterization of MA in Leishmania and pave the way for further functional studies. Graphical Abstract: Graphical Movie Abstract: